DETERMINAN PERTUMBUHAN EKONOMI KABUPATEN/KOTA PROVINSI BALI - Diah Ambarwati (2022)
This research aims to determine Domestic Investment (PMDN), Foreign Investment (PMA), the number of tourist, the number of unemployed and interest rate as a control variable on economic growth which is described by PDRB in all districts/cities in the Province of Bali. The sampling in this research used saturated sampling technique in 9 regions during 2011-2020, so a total of sample of 90 data was obtained from the Central Bureau of Statistics (BPS). This research uses panel data analysis by combining time series data and cross section data. The result partially show that PMA and the number of tourist have a significant positive effect on PDRB, interest rates have a significant negative effect, while PMDN and the number of unemployed have no effect on PDRB. The result of the research simultaneously show that PMDN, PMA, number of tourist, number of unemployed, and interest rates have an effect on PDRB or economic growth. Keywords: Economic Growth, Domestic Investment, Foreign Investment, Number of Tourist, Number of Unemployed, Interest Rate.